PERANCANGAN TRANSMISI MESIN PEMBUAT PAGAR KAWAT HARMONIKA - Putra Pratama, Adytia; Julian Robi Pratama; Ulikaryani; Jenal Sodikin (Politeknik Negeri Cilacap, 2024)
Zig-zag wire or what is usually caleed harmonica wire can be used to make fences. Making harmonica wire is doen by bending the wire into a zig-zag shape. The process of making harmonica wire fences can be used as a home industry production. Therefore, the aim of this research is to design the transmission components of the harmonica wire fence making machine by calculating the machine elements in the transmission. The research method uses the VDI 2222 method approach. The design results are in the form of a harmonica wire fence making machine. The results of calculating the machine elements on the harmonica wire fence making machine have results including the transmission pulley used, namely type A with sizes 4 inches and 14 inches, the v-belt used is type A belt with a belt circumference length of 76 inches. Meanwhile, the diameter of the shaft used in the harmonica wire fence making machine is 25 mm with S45C material and the estimated force required in bending the the wire is 7.27 N.